El tractament de la variació lèxica en el Diccionari català-castellà i castellà-català de Francesc de Borja Moll - Vicente Llavata, Santiago (Studia Romanica Posnaniensia, 2025)
In 1977, Francesc de Borja Moll published the Catalan-Spanish/Spanish-Catalan Dictionary in the context of the linguistic and cultural adjustment of the Balearic islands. Since then, several editions of this lexicographical work have been published. The aim of this paper is to analyze, from a contrastive and integrated perspective, the treatment of lexical variation in these lexicographical work. The study will focus on the representation of the different geolectal varieties of Catalan in terms of lexical presence, with a special focus in the linguistic areas that are little represented in the history of Catalan lexicography, such as the Catalan of the Franja. The results may be of interest for theoretical reflection on variation and linguistic change, considering that this dictionary will soon be 50 years old.